2022
DOI: 10.2174/1389200223666220905162245
|View full text |Cite
|
Sign up to set email alerts
|

Effective Cancer Management: Inimitable Role of Phytochemical Based Nano- Formulations

Abstract: Background: Global cancer statistics defines the severity of disease even after significant research worldwide. Problem: Failure of the currently available treatment approaches including surgery, radiation therapy and traditional chemotherapy. Aim: The aim of this review is to discuss the role of phytochemical based nano-formulations for treatment of cancer. Discussion: In the past few decades, phytochemicals have gained popularity for acting as a potential anticancer treatment with low systemic toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…An extensive literature search indicated that there has been an increased trend in phytochemical-based nanoformulation research, which has been widely investigated against various cancers. ,, From a pharmacological perspective, phytonanomedicine prevents the external degradation of bioactive molecules, simultaneously improves drug stability and physicochemical properties, and collectively enhances the anticancer efficiency of a native phytochemical . Recently, Javed et al reviewed various nanoformulations of the phytochemical apigenin that have significantly increased therapeutic efficacy and antitumor activity in a variety of malignancies by improving bioavailability over native apigenin .…”
Section: Opportunities For Phytonanomedicine In Cancer Therapymentioning
confidence: 99%
“…An extensive literature search indicated that there has been an increased trend in phytochemical-based nanoformulation research, which has been widely investigated against various cancers. ,, From a pharmacological perspective, phytonanomedicine prevents the external degradation of bioactive molecules, simultaneously improves drug stability and physicochemical properties, and collectively enhances the anticancer efficiency of a native phytochemical . Recently, Javed et al reviewed various nanoformulations of the phytochemical apigenin that have significantly increased therapeutic efficacy and antitumor activity in a variety of malignancies by improving bioavailability over native apigenin .…”
Section: Opportunities For Phytonanomedicine In Cancer Therapymentioning
confidence: 99%
“…In addition, the poor solubility/ stability, nontargeting capability, and uncontrollable release of CPT also hinder its anticancer efficacy, and it even causes side effects in normal tissues. [9][10][11][12][13][14] In the past decades, researchers have investigated numerous methods and materials for chemotherapeutic drug delivery, which have given rise to optimism for the effective treatment of cancer. Advances in recent research have demonstrated that liposomes and cyclodextrins can be used for the delivery of CPT to reduce its toxicity and promote its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in recent research have demonstrated that liposomes and cyclodextrins can be used for the delivery of CPT to reduce its toxicity and promote its properties. [15][16][17][18][19][20][21][22][23] However, most of these carriers do not meet the requirements of a high drug-delivery efficiency, ease of dispersion, and controlled particle size, which are key to clinical translation. 24,25 Calixarene (CA), a crucial component of supramolecular families, is a supramolecular macrocyclic compound made of phenol units connected by methylene bridges, with an easy chemical modification of the upper and lower edges of the phenol units, an adjustable size, and conformation of the hydrophobic cavities in the structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations